FDI and domestic economy: neoliberalism in China - Chandra, Nirmal Kumar (1999)
This paper explores the complexity of China's FDI policy. Beginning with the size of inflows and their distribution by sector, host region and source country, it goes on to describe the changing policies and the new types of foreign firms emerging in the recent past. A critical look at official data suggests an exaggeration of the stock of inward FDI and an understatement of FDI outflows, which is often misconstrued as capital flight. This leads to a discussion of the role of FDI in China's economy. - Reproduced
Keywords: Foreign investment